Sistem Informasi Akuntansi Penggajian Pegawai Pada Badan Kepegawaian Negara Kantor Regional VI Medan - Muhammad Rifana; Nur Fadhillah Ahmad Hasibuan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study is to find out and assess whether the implementation of Payroll Accounting Information System set at regional Office VI of the Medan State Personnel Agency (BKN) has been conducted effectively. The type of research used is Qualitative Descriptive Research, which focuses on payroll infprmasi system at Regional Office VI of The State Personnel Agency (BKN) Medan. Data collection techniques used are by interview method, and other supporting techniques are observation and documentation. The results of this study prove that the Accounting Information System with regard to payroll procedures at the Regional Office VI of the State Personnel Agency (BKN) Medan has been running effectively. Can be seen from the act of cheating that never happened in the office. And it is in accordance with the program that has been adjusted by the regulations set by the government, also has data on basic salaries, allowances and deductions issued by the Regional Office VI of the State Personnel Agency (BKN) Medan. Accounting information system in the form of attachment of parent salaries based on class in Regional Office VI of the State Personnel Agency (BKN) Medan has been easy to understand by the employees who receive salaries. Accounting recording used in the Payroll system at Regional Office VI of the State Personnel Agency (BKN) Medan is an account of Employee Salary Expenditure and Salary Cart (Salary Slip).